Allostatic load index across the psychosis spectrum: a systematic review and meta-analysis - Madaria, Lander; Aymerich, Claudia; Pedruzo, Borja; Salazar de Pablo, Gonzalo; Alonso-Alconada, Daniel; Fusar-Poli, Paolo; Gonzalez-Torres, Miguel Ángel; Catalan, Ana (Frontiers in Psychiatry, 2025)
BackgroundIndividuals diagnosed with schizophrenia spectrum disorders experience significantly higher morbidity and mortality rates than the general population, with evidence of multisystemic alterations. The concept of allostatic load (AL) provides a framework for understanding the cumulative physiological burden imposed by chronic stress. This burden is quantified using the AL index, which integrates multiple biomarkers to assess the impact of prolonged stress on various physiological systems. This review aims to measure the difference in the AL index between individuals with psychosis and the general population, as well as to evaluate the methods used to assess AL in this population.MethodsA PRISMA/MOOSE-compliant systematic search was conducted in the Web of Science, PubMed, BIOSIS, KCI-Korean Journal Database, MEDLINE, Russian Science Citation Index, SciELO, and Cochrane Central Register databases from inception to January 28th, 2025. Studies reporting on the AL index of individuals with psychosis or clinical high risk of psychosis (CHR-P) compared to healthy controls (HC) were included. We used random effects meta-analysis to evaluate: (1) differences between patients with a chronic schizophrenia spectrum disorder (C-SSD) or first-episode psychosis (FEP), compared to healthy controls (HC); (2) differences between patients with C-SSD and FEP. We conducted quality assessment, heterogeneity, publication bias, and meta-regression analyses (PROSPERO: CRD 42024579704).ResultsFrom 922 citations, five studies were included (N=669), showing a higher AL in individuals with psychosis (C-SSD, k=3; g= 1.3315; 95% CI: 0.9679–1.6951; FEP, k=4; g = 0.5464; 95% CI, 0.0698 to 1.0230) compared to HC. The AL index was also higher in patients with C-SSD compared to FEP (k=3; g = 0.8196; 95% CI, 0.2977 to 1.3415). No CHR-P data were found for analysis. Different methods for computing the AL index were observed.ConclusionAllostatic load seems higher in individuals with psychosis compared to the general population, with chronic conditions exhibiting higher allostatic load than the early stages of the disorder. However future research is needed to consolidate these emerging trends.